Question Types on Reading Comprehension in TOEFL Test: An Implication in Teaching Reading TOEFL to Students - Fitria, Tira Nur (Journal of English and Education (JEE), 2024)
Reading section in TOEFL is challenging because there are many texts and test items to be completed in a relatively short time. Thus, test-takers should read quickly and precisely. This study describes the types of reading comprehension in Pre-Test and Post-Test TOEFL and its implications in teaching reading TOEFL. This research is descriptive and qualitative. The result analysis shows that several types of reading questions in Pre-Test and Post-Test TOEFL are 1) idea of passage questions, 2) directly answered questions, 3) indirectly answered questions, 4) vocabulary questions, and 5) overall review questions. When teaching TOEFL reading to students, it is important to employ several general strategies. These include introducing the various categories of reading questions, followed by questions that refer to specific sentences in the reading. Additionally, providing explanations on how to answer the questions is essential for effective comprehension. The TOEFL reading teaching strategy involves introducing various types of reading questions, and exercises that refer to certain sentences in the reading, as well as providing explanations on how to answer the questions. Through this approach, students can gain a better understanding of the structure and types of questions that may appear in the TOEFL exam.